Večja mesta Slovenije kot okoljsko problemska območja - Plut, Dušan (Geographica Slovenica, 2000)
Slovenia is characterised by rather low urbanisation level (50% of inhabitants) and, from the European point of view, small cities. Due to great landscape sensitiveness of big cities and over-burdening, also in nineties individual city components in most regional centers were excessively or critically polluted, with the accent on the running waters. In most cities there was no secondary cleaning of waste waters or separate collecting of wastes, and also rapid increase of negative landscape consequences of the uncontrolled suburbanisation and increase of the city road traffic is significant.
Keywords: geografija naselij; mesta; urbani razvoj; sonaravni razvoj; sustainable development; trajnostni razvoj; ecology; ekologija; Slovenia; Slovenija